The development of a specialty: an interview with Dr. Mark C. Rogers, a pioneering pediatric intensivist. Issue 9 (28th July 2014) - Mai, Christine L.; Firth, Paul G.; Ahmed, Zulfiqar; Rodriguez, Samuel; Yaster, Myron; Timeline Podcasts
Summary Dr. Mark C. Rogers (1942–), Professor of Anesthesiology, Critical Care Medicine, and Pediatrics at the Johns Hopkins University, was recruited by the Department of Pediatrics at Johns Hopkins Hospital in 1977 to become the first director of its pediatric intensive care unit. After the dean of the medical school appointed him to chair the Department of Anesthesia in 1979, Rogers changed the course and culture of the department. He renamed it the Department of Anesthesiology and Critical Care Medicine, and developed a long‐term strategy of excellence in clinical care, research, and education. However, throughout this period, he never lost his connection to pediatric intensive care. He has made numerous contributions to pediatric critical care medicine through research and his authoritative textbook, Rogers' Textbook of Pediatric Intensive Care. He established a training programme that has produced a plethora of leaders, helped develop the pediatric critical care board examination, and initiated the first World Congress of Pediatric Intensive Care. Based on a series of interviews with Dr. Rogers, this article reviews his influential career and the impact he made on developing pediatric critical care as a specialty.